2022
DOI: 10.3390/bioengineering9080392
|View full text |Cite
|
Sign up to set email alerts
|

Novel Gene-Correction-Based Therapeutic Modalities for Monogenic Liver Disorders

Abstract: The majority of monogenic liver diseases are autosomal recessive disorders, with few being sex-related or co-dominant. Although orthotopic liver transplantation (LT) is currently the sole therapeutic option for end-stage patients, such an invasive surgical approach is severely restricted by the lack of donors and post-transplant complications, mainly associated with life-long immunosuppressive regimens. Therefore, the last decade has witnessed efforts for innovative cellular or gene-based therapeutic strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 221 publications
0
1
0
Order By: Relevance
“…Liver transplant has shown promise in attenuating symptoms and helping normalize BCAA homeostasis and may be an option for some patients 32,33 . The benefits observed in some patients with liver transplant suggest that liver‐directed gene therapy also may hold promise as a treatment for MSUD 34,35 . Ultimately, an interventional therapy that alleviates the lifelong burden of dietary restrictions and concomitantly prevents or treats metabolic decompensation episodes would drastically improve patient morbidity and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplant has shown promise in attenuating symptoms and helping normalize BCAA homeostasis and may be an option for some patients 32,33 . The benefits observed in some patients with liver transplant suggest that liver‐directed gene therapy also may hold promise as a treatment for MSUD 34,35 . Ultimately, an interventional therapy that alleviates the lifelong burden of dietary restrictions and concomitantly prevents or treats metabolic decompensation episodes would drastically improve patient morbidity and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to block the inhibitory action of humoral and cell-mediated immunity towards these gene vectors are currently being investigated [84]. Further information is outside the scope of this review, and further discussion can be found in the following recent review [85].…”
Section: Gene Therapy For Metabolic Liver Diseasementioning
confidence: 99%